Preparation and properties of multifunctional polyaspartic acid/waste paper fiber-based superabsorbent composites. Issue 5 (October 2022) - Sang, Wutang; Cui, Shuzhen; Wang, Xiangbing; Liu, Bei; Li, Xiaoxia; Sun, Kanjun; Peng, Hui; Ma, Guofu
Abstract: Superabsorbent composites (SACs) are widely used for agricultural applications acts as a "miniature soil moisture reservoir" for plants. While these substrates have excellent water retention properties, they often suffer from production costs and a variety of environmental challenges. Herein, polyaspartic acid (PASP), waste paper fibers (WPF) and 2-acrylamido-2-methyl-1-propanesulfonic acid (AMPS) graft copolymerize acrylic acid (AA) to prepare a novel multifunctional PASP-g-P(AA-co-AMPS)/WPF SACs. The synthesis conditions use to prepare the PASP-g-P(AA-co-AMPS)/WPF SACs are optimized, including PASP content, mass ratio of AMPS and AA, initiator content and cross-linker content. In addition, the water retention, salt and acid resistance, reversible swelling and temperature sensitivity of SACs are also investigated and analyzed in detail. Due to the uniform distribution and the rich pore structure, it has a maximum equilibrium adsorption capacity of optimal SACs in distilled water, tap water and NaCl solution (0.9 wt%) are determined to be 731.0 g g −1, 189.2 g g −1 and 81.4 g g −1, respectively. Thus, PASP-g-P(AA-co-AMPS)/WPF SACs exhibit excellent environmental tolerance and provide a promising strategy for sustainable agriculture and desertification control. Graphical Abstract: ga1 Highlights: Providing a method for utilizing WPF. A novel SACs synthesized using PASP and WPF. SACs with excellent water retention and repeating water absorption. SACs with favorable temperature sensitivity.